The Impact of Parental Opioid Use Disorder on Children in Rural Texas. (1st June 2022) - Gary, Jodie C.; Downing, Nancy R.; Pittman, Alison
Abstract: Introduction: The impact of opioid use disorder (OUD) on children is of increasing concern to providers and communities and is yet to be fully understood. Children and families in rural areas are particularly vulnerable due to decreased access to care, lower socioeconomic status, and lower rates of health insurance coverage. This qualitative secondary data analysis of transcripts from interviews with community stakeholders specifically examined responses when asked how parental OUD impacted children in their rural communities. Methods and Materials: As part of a larger community assessment, 11 focus group and three individual interviews with a variety of stakeholders most likely to encounter those with or at risk for substance use disorder from a predominately rural region of Texas were held in October of 2019. During one-hour sessions a scripted interview guide was used to ask open-ended questions to identify the prevalence and impact of OUD within the community. Transcripts of recorded interviews were coded by three researchers using conventional content analysis focusing on discussion of how parental OUD impacted children in their rural communities. Codes were classified into themes based on consensus. Results: Identified themes were (1) Community Concern for Families; (2) Impaired Parents, Neglected Children, and (3) Intergenerational Normalization of Substance Misuse. Conclusions: The impact of parental OUD and SUD was a concern for participants. Findings have implications for strategies to prevent and mitigate adverse outcomes for children and families in rural areas.